2009
DOI: 10.1002/rmv.615
|View full text |Cite
|
Sign up to set email alerts
|

Function of human cytomegalovirus UL97 kinase in viral infection and its inhibition by maribavir

Abstract: Summary The serine/threonine kinase expressed by human cytomegalovirus from gene UL97 phosphorylates the antiviral drug ganciclovir, but its biological function is the phosphorylation of its natural viral and cellular protein substrates which affect viral replication at many levels. The UL97 kinase null phenotype is therefore complex, as is the mechanism of action of maribavir, a highly specific inhibitor of its enzymatic activity. Studies that utilise the drug corroborate results from genetic approaches and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
131
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 148 publications
(214 reference statements)
2
131
0
2
Order By: Relevance
“…An indirect nuclear transport mechanism could result from interaction of pUL97 with a nuclear cellular protein, such as the retinoblastoma protein (Rb) which contains a strong importin-a-driven NLS (Fontes et al, 2003). However, although motifs involved in the regulation of Rb phosphorylation through pUL97 were described (Gill et al, 2009;Prichard, 2009;Prichard et al, 2008), a direct binding of Rb to pUL97 has not been demonstrated yet. Another factor impacting on the regulation of nuclear translocation may be provided through the pronounced autophosphorylation activity of pUL97.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An indirect nuclear transport mechanism could result from interaction of pUL97 with a nuclear cellular protein, such as the retinoblastoma protein (Rb) which contains a strong importin-a-driven NLS (Fontes et al, 2003). However, although motifs involved in the regulation of Rb phosphorylation through pUL97 were described (Gill et al, 2009;Prichard, 2009;Prichard et al, 2008), a direct binding of Rb to pUL97 has not been demonstrated yet. Another factor impacting on the regulation of nuclear translocation may be provided through the pronounced autophosphorylation activity of pUL97.…”
Section: Discussionmentioning
confidence: 99%
“…HCMV replication is restricted to specific host-cell types and is dependent on the balance of interactions between viral and cellular proteins. In this regard, various virus-or cell-encoded protein kinases display crucial functions during HCMV replication and are interlinked in several aspects of their regulatory properties (Prichard, 2009;Lee & Chen, 2010). The serine/threoninetype protein kinase pUL97 is an important determinant of efficient HCMV replication.…”
Section: Introductionmentioning
confidence: 99%
“…Infection with the prevalent β-herpes virus human cytomegalovirus (HCMV) induces increased levels of protein phosphorylation and markedly alters host cell signal transduction pathways (1). A portion of the phosphorylation changes induced by HCMV infection are attributed to the Ser/ Thr kinase encoded by the viral genome, pUL97 (2), and others may derive from cellular kinase(s) packaged into virions (3) or from cellular kinases known to be activated by HCMV (4).…”
mentioning
confidence: 99%
“…The lead compound in this group is maribivir (5,6-dichloro-2-(isopropyl)amino-1-(l-ribofuranosyl)benzimidazole), which is a highly specific inhibitor of the UL97 kinase. Evidence suggests that inhibition of UL97 results in defective viral encapsidation, hinting at a possible role for this kinase at the stage of nuclear egress (Krosky et al, 2003), although the functions of the UL97 kinase appear to be numerous (Prichard, 2009). Plaque reduction assays have shown that maribavir has five-fold greater activity against viral replication in some laboratory strains of CMV when compared with GCV .…”
Section: Benzimidazole Ribonucleosidesmentioning
confidence: 99%